Differential behavioral profile induced by the injection of dipotassium chlorazepate within brain areas that project to the nucleus accumbens septi. - Llano López, Luis H. (2013)
The effect of the agonism on g-aminobutyric acid (GABA) receptors was studied within medial prefrontal cortex (mPFC), amygdala (AMY) and ventral hipocampus (VH) in the plus-maze test in male rats bilaterally cannulated. These structures send glutamatergic projections to the nucleus accumbens septi (NAS), in which interaction and integration between these afferent pathways has been described. In a previous study of our group, blockade of glutamatergic transmission within NAS induced an anxiolytic like effect. Methods: Three rat groups received either saline or dipotassium chlorazepate (1 or 2 μg/1 μl solution) 15 min before testing. Time spent in the open arms (TSOA), time per entry (TPE), extreme arrivals (EA), open and closed arms entries (OAE, CAE) and relation- ship between open- and closed-arms quotient (OCAQ) were recorded. Results: In the AMY injected group TSOA, OAE and EA were increased by the higher doses of dipotassium chlorazepate (p < 0.01). In the mPFC, TPE was decreased by both doses (p < 0.05). Injection within ventral hippocampus (VH) decreased TSOA, OAE and OCAQ with lower doses (p < 0.05). When the three studied saline groups were compared, TSOA, OAE, EA and OCAQ were en- hanced in the VH group when compared to mPFC and AMY (p < 0.001). Insertion of inner canula (p < 0.001, p < 0.01, p < 0.01) and saline injection showed an increasing significant difference (p < 0.001 in all cases) with the action of guide cannula alone within VH in TSOA, OAE and EA. Conclusion: We conclude that the injection of dipotassium chlorazepate has a differential effect depending of the brain area, leading to facilitatory and inhibitory effects on anxiety processing.